The works of Aurelius Augustine, Bishop of Hippo: a new translation - Augustine, Saint, Bishop of Hippo. (T. and T. Clark, 1871)
v.1-2. The city of God--v.3. Writings in connection with the Donatist controversy--v.4. The anti-Pelagian works, pt.1--v.5. Writings in connection with the Manichaean heresy--v.6. Letters, pt.1--v.7. On the Trinity--v.8. The sermon on the Mount expounded, and The harmony of the evangelists--v.11. Lectures on tractates on the Gospel according to St. John, pt.2--v.12. The anti-Pelagian works, pt.2.